3‐3: Study on the Field of View Properties for a Holographic Waveguide Display System. Issue 1 (May 2016) - Weng, Yishi; Zhang, Yuning; Li, Xiaohua
Abstract : The Field of View (FOV) properties and effects of the reflection Volume Holographic Grating (VHG) in conical mounting was studied when used in a see through Head Mounted Display in detail. Also, two methods for enlarging the FOV and improving the color uniformity for reflection VHG were analyzed and simulated.